GAP Analysis Untuk Mengetahui Kinerja Implementasi Program Merdeka Belajar Kampus Merdeka - Mutmainah, Isbandriyati; Yulia, Iis Anisa; Marnilin, Feni; Mahfudi, Ahmad Zaid (Jurnal Ilmiah Manajemen Kesatuan, 2022)
ABSTRACT This study aims to analyze the performance of the MBKM Economiic Faculty Nusa Bangsa University’s program implementation. The analytical method used are gap analysis and paired sample t-test by comparing student perceptions of student performance and student expectations of the importance of MBKM implementation and Economiic Faculty services in the MBKM program. The sampling method is saturated sampling, and the number of respondents is 142 students. By using gap analysis, the results showed that there was a gap between the perceived performance of students and expectations of the level of importance in both the implementation of the MBKM program and the quality of Economiic Faculty services in the implementation of MBKM. By using a different paired sample t-test, the results showed that there was a significant difference between the perceived performance of students and the level of importance of the MBKM program both in the implementation and quality of FEB services in the implementation of MBKM. The management of Economiic Faculty UNB needs to carry out a planned and structured evaluation of the implementation of the MBKM program so that the objectives of the program that are already good, can be implemented properly, and need to involve students in determining the MBKM program that is held so that there is harmony between the wishes of the manager and the needs of students regarding the benefits that will be obtained from student participation in the MBKM program. Keywords: Importance, Performnace, Service Quality, MBKM